2023
DOI: 10.1038/s41598-023-32798-9
|View full text |Cite
|
Sign up to set email alerts
|

LPS induces microglial activation and GABAergic synaptic deficits in the hippocampus accompanied by prolonged cognitive impairment

Abstract: Neuroinflammation impacts the brain and cognitive behavior through microglial activation. In this study, we determined the temporal sequence from microglial activation to synaptic dysfunction and cognitive behavior induced by neuroinflammation in mice. We found that LPS injection activated microglia within a short period, followed by impairments in GABAergic synapses, and that these events led to long-term cognitive impairment. We demonstrated that, 3 days after LPS injection, microglia in the hippocampus were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…5A), suggesting that rod-like microglia may be engaged in separate, delayed waves of repair after inflammation in the brain in the switch from an immune trained to tolerized state after the resolution of cytokine responses and obvious sickness behaviors. This could explain the short-term learning and memory impairments described by Jung et al, 2023 (73), which were observed at 6 days after LPS, and why we failed to observe them in our study in which behavioral testing was performed weeks after LPS.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…5A), suggesting that rod-like microglia may be engaged in separate, delayed waves of repair after inflammation in the brain in the switch from an immune trained to tolerized state after the resolution of cytokine responses and obvious sickness behaviors. This could explain the short-term learning and memory impairments described by Jung et al, 2023 (73), which were observed at 6 days after LPS, and why we failed to observe them in our study in which behavioral testing was performed weeks after LPS.…”
Section: Discussioncontrasting
confidence: 43%
“…(14,72) Once immune signaling molecules reach the brain parenchyma, they can bind to cytokine receptors expressed on both neurons and glial cells to directly or indirectly modulate neuronal firing properties, which could ultimately shape circuit function and downstream behavior. (14) A recent study using the same repeated low-dose LPS model (73) defined a temporal sequence after 2xLPS by which changes in microglia morphology, density, and expression of phagocytic markers precedes GABAergic synapse loss, followed by memory impairment on the novel object recognition task. However, this study focused on short-term changes within a range of 6 days post-2xLPS, and investigation into the prolonged effects of repeated low-dose LPS on behaviors long after recovery had yet to be thoroughly examined.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to increased energetic demand, oxygen extraction from the blood is also likely enhanced by increased permeability across the blood brain barrier (BBB) and the multifaceted actions of immune cells. Numerous studies have demonstrated that LPS administration yields dramatic increases in spontaneous calcium spiking and excitatory post-synaptic currents from neurons in the cortex, hippocampus, and several other regions of the brain, while also reducing the activity of inhibitory GABAergic interneurons [ 55 , 86 , 89 – 94 ]. Because restoration and maintenance of ion gradients accounts for the bulk of ATP consumption in the brain, and energy consumption increases markedly with increased action potential frequency, inflammation-induced neuronal hyperactivity across different brain regions constitutes a massive additional energetic burden [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Capitalizing on the technique’s penetration depth and unparalleled spatial resolution, we quantified layer-specific differences in vascular oxygen extraction and capillary flux provoked by a prolonged inflammatory threat. Microvascular pO2 and capillary RBC flux measurements were collected from cortical layers I-IV before, during, and after 14 days pro-inflammatory stimulus, induced by daily intraperitoneal injection of the bacterial endotoxin Lipopolysaccharide (LPS) [ 51 55 ]. The measurements were used to compute layer-specific changes in oxygen extraction and capillary red blood cell flux.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we describe an accessible and open-source morphology analysis toolset: MicrogliaMorphology (ImageJ tool) and MicrogliaMorphologyR (R package), which supplies the field with new tools to systematically evaluate the heterogeneity of microglia morphological states by considering 27 different measures of microglia morphology. To demonstrate use cases for our toolset, we characterized and analyzed microglia morphology in an experimental model of repeated immune stimulation by peripheral lipopolysaccharide (LPS) administration, a commonly used model (H. Jung et al, 2023; Wendeln et al, 2018) which induced population shifts in the four major classes of microglia morphology in our dataset: ramified, hypertrophic, ameboid, and rod-like. Application of MicrogliaMorphology and MicrogliaMorphologyR by the scientific community will yield novel insights into microglia morphology differences in the brain at a single-cell resolution and in a spatially-resolved manner across various experimental models and research questions.…”
Section: Introductionmentioning
confidence: 99%